Transcriptomic insights into arabinogalactan protein mechanism of action in galactosyltransferase octuple mutants - Ayorinde, Damilola A.; Olanrewaju, Gbolaga O.; Showalter, Allan M. (Frontiers in Plant Science, 2026)
Arabinogalactan-proteins (AGPs) are a family of hyperglycosylated hydroxyproline-rich glycoproteins essential for plant growth and development and generally contain 10% protein and 90% carbohydrate. Eight galactosyltransferases (GALTs), specifically GALT2-GALT9, catalyze galactose addition to hydroxyproline residues in the AGP protein backbone and initiate glycosylation of AGPs. Arabidopsis galt octuple mutants that result from the knockout of eight GALT genes displayed severe phenotypic changes, prompting our exploration of the mechanisms of action of AGPs by comparing the transcripts of galt octuple mutant flowers and siliques to wild type flowers and siliques in Arabidopsis thaliana. Transcriptomic analysis of flowers from galt octuple mutants revealed 930 significantly differentially expressed genes (426 upregulated, 504 downregulated). Many of the downregulated genes are reported to be crucial for pollen tube growth, pollination, and flower development. In siliques, there were 1,476 significantly differentially expressed genes (1,027 upregulated, 449 downregulated), including the downregulation of genes for pectin methyl esterase inhibitors (PMEIs) and suspensor development. There were 45 genes commonly downregulated in flowers and siliques, which are reportedly crucial for glycosylation, glycoprotein synthesis, and cell wall modification. On the other hand, there were 194 commonly upregulated genes linked to calcium ion binding with kinases and phosphatases in the signal transduction pathways, cell-cell communication, stress response and pathogen defense response regulation in both flowers and siliques. These findings offer insights into plant molecular responses to AGP dynamics and provide a foundation for further investigations into the underlying mechanisms of action of AGPs by revealing the genes and pathways related to AGP function, suggesting that AGPs may mediate the effects of these genes or pathways, in part, by influencing signal transduction pathways involving kinases and phosphatases.